Role of Purpose in Leadership Effectiveness - Vaid, Percy (Global journal of Business and Integral Security, 2024)
This research aims to explain the role and impact of purpose on leadership effectiveness in India. For a long time, meaningful purpose has been associated with leading a good satisfying, and productive life, however the same has not been explored enough about leadership. This area of leadership merits further research to gain a deeper understanding of the cause-and-effect relationship between leadership and purpose. Deeper insights into this connection would help industry professionals design better leadership development and executive coaching interventions, to enhance overall business effectiveness and achievement of organizational goals. Understanding these areas would also assist in the development of a culture that focuses on leadership development and not only on leader development. Through a combination of research, studies and qualitative surveys, this research will attempt to understand the role of purpose in leadership effectiveness and try to uncover, key elements that can help in the design of better coaching and development interventions.